Storage Ratio of CO2 Miscible Flooding in Chang 8 Reservoir of H Block in Ordos Basin Under Different Injection Methods - Zhang, Yi; Zhang, Bin; Yang, Yongzhi; Liu, Banghua; Shen, Lei (Frontiers in Energy Research, 2022)
Carbon dioxide is a typical kind of greenhouse gases, and the oil and gas field recovery ratio could be significantly improved by injecting it into the formation. The main goal is to increase the recovery ratio in the early stage of studying gas injection miscible flooding. With the advancement of the “carbon neutral” strategy in China, the application of CO2 miscible flooding technology, which aims to enhance the oil recovery ratio in Chinese oilfields, has been further expanded. The development concept needs to change from simply improving the recovery ratio to improving both the recovery ratio and the CO2 storage ratio. In the current CO2 flooding research, people mainly focus on the improvement of the recovery factor, and less attention is paid to the underground storage of CO2. In order to further study the relationship between the displacement efficiency of CO2 and the storage situation, this paper innovatively combines the storage ratio and storage amount of CO2 with the recovery factor. A number of parameters under different injection methods in the study area were calculated, providing a new research angle for the study of CO2 displacement. Take Chang 8 reservoir in Block H of Ordos Basin as an example. Firstly, the minimum miscibility pressure (MMP) of CO2 at formation temperature was measured by the slim tube experiment according to the reservoir pressure status to judge the CO2 flooding status in the study area. Then, the numerical simulation model of the study area was established, and the historical fitting was completed according to the existing CO2 flooding test wells. The reservoir numerical simulation is used to study the recovery ratio and CO2 storage ratio under different CO2 miscible flooding, including different injection rates, injection sequences, and bottom hole pressures. The results show that the MMP of CO2 in the study area is between 12.65 and 14.80 MPa, which means the CO2 flooding state in this area is miscible flooding with high oil displacement efficiency. The CO2 storage ratio at 5–40 t/d CO2 injection rate is between 54.02% and 64.38% after 20 years, and the CO2 storage ratio is larger when the gas injection rate is 10 t/d. In combination with CO2 storage capacity and the oil recovery factor, it is recommended that the gas injection rate of a single well in the study area is 20–30 t/d. The CO2 storage ratio after 20 years under different gas injection sequences is 57.69%–61.27%. It is suggested that the study area should be injected with water and gas alternately after 2 years of gas injection. When continuous gas injection is used, the CO2 storage ratio under different production well bottom hole pressures is between 54.95% and 59.82%. It is recommended that the bottom hole flow pressure in the study area be maintained at between 9 and 10 MPa. The results show that the main factor that affects the annual CO2 storage ratio in the study area is the CO2 injection rate. Gas injection rate, injection sequence, and bottom hole pressure of production wells will all have an impact on the overall storage ratio. And alternate water and gas injection is quite significant. From the perspective of storage ratio, the optimal CO2 miscible flooding injection method has been optimized for the study area, which provides a reference for the implementation of CO2 underground storage technology in mines.